PERANAN PEMBERIAN KOMPENSASI DALAM MENINGKATKAN SEMANGAT KERJA KARYAWAN BAGIAN PRODUKSI PADA CV BOGA JAYA (AMANDA BROWNIES) BANJARBARU - Ricky Agus Ariandy; Rizki Amalia Afriana; Dewi Setiawati (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
The purpose of this study is to determine the compensation that has been carried out by CV Boga Jaya (Amanda Brownies) Banjarbaru in increasing employee morale and to find out the compensation that CV Boga Jaya (Amanda Brownies) Banjarbaru should always do in increasing employee morale. The method used in this study is qualitative descriptive method. This method was chosen considering that this study aims to make an overview of compensation in improving employee morale at CV Boga Jaya (Amanda Brownies) Banjarbaru. The results of the study found that employee morale is still low, this can be seen from the results of the questionnaire answers. Based on these results, it is known that compensation has not been given appropriately, such as compensation is still inadequate which results in a decrease in employee morale, the workload felt by employees is still quite high and conflicts due to compensation that is considered still unfair and decent.